Serum Creatine Kinase-MB Levels in Elderly Patients After Hemorrhagic and Ischemic Stroke Without a History of Heart Disease - Mariel Daba; Nathasya Ferdyastari (Biomedical Journal of Indonesia, 2026)
Introduction. Elevations in cardiac biomarkers such as creatine kinase-MB (CK-MB) have been reported in stroke patients, even without clinical signs of heart disease. CK-MB, a cardiac-specific isoenzyme, indicates myocardial stress or injury. Exploring CK-MB dynamics in elderly post-stroke patients may provide insights into cardiovascular risk and prognosis. Methods. This comparative analytical cross-sectional study involved two groups of stroke patients admitted to Sentra Medika Hospital, Cikarang: hemorrhagic stroke (n=8) and ischemic stroke (n=8), totaling 16 participants. Inclusion criteria were age ≥60 years, stroke history within 3–6 months, and no cardiovascular disease based on medical records. Venous blood samples were collected to measure serum CK-MB levels using ELISA. Data were analyzed with an independent sample t-test. Results. A significant difference in mean CK-MB levels was observed (p=0.03). The hemorrhagic group had a mean CK-MB of 29 U/L, while the ischemic group had 26 U/L. Both values exceeded the reference level of <25 U/L, showing elevated CK-MB in both stroke types. Conclusion. Serum CK-MB levels were significantly elevated in elderly patients after hemorrhagic and ischemic stroke compared with normal values, suggesting CK-MB as a potential clinical marker in post-stroke patients.